Land and property institutions: Endogenous origins and equilibrium effects - Catherine Boone (London School of Economics and Political Science (LSE), Department of International Development, 2015)
The idea of the state in Africa as institutionless underlies much contemporary theorizing about African politics. The term "neopatrimonialism" - widely employed in the comparative politics literature to describe African political systems - implies lack of institutionalization, centralization of power in the hands of a supreme ruler, and government through personalized, shifting networks. The counterpart of this idea is institution-less conceptualization of society, and most importantly perhaps, of rural society, which accounts for 50-90% of the total population of almost all African states. This paper reverses this image of structure-less states and societies. It focuses on rural land tenure institutions and argues that they are the product of institution-building strategies of Africa's modern rulers, both colonial and postcolonial.
Keywords: 330; Africa; Neopatrimonialism; Land-tenure; Institution; Rural society